Preparation and evaluation of a liquid fertilizer from lactic fermentation of weeds - Dominguez, Elizabeth Bereníce Chihuan; Morales , Juan Gabriel Juscamaita; Tejada, Jorge Luis; Ticllahuanaco, Edgar Huamani (Revista de Ciências Agroveterinárias, 2023)
A total of twenty mixtures of weed, B-Lac and molasses were prepared in order to evaluate an accelerated liquid fertilizer (ALF) based on these plants. A mixture of 85% weed: water (1:1), 10% molasses and 5% B-Lac showed the best characteristics and was reproduced at a pilot scale. ALF was applied to lettuce using the following treatments: one foliar application per week of 10 mL L-1 (FA1), two foliar applications per week of 10 mL L-1 (FA2), one drench application of 50 mL L-1 every week (DA1), a drench application of 50 mL L-1 every two weeks (DA2) and a control without application (CWA). The variables evaluated were total yield, commercial yield, fresh weight, height, head diameter, percentage of dry matter and the concentration of foliar nitrogen, phosphorus, and potassium. The mixtures in the laboratory and pilot phase were evaluated in a completely randomized design. The field phase was assessed in a completely randomized block design with five treatments and four replications. No significant differences were found between the treatments, except in the percentage of dry matter and potassium content, where FA2 showed the best results (2.35% and 541 mg plant-1, respectively). The highest total yield (26.4 t ha-1) and commercial (24.11 t ha-1) were achieved with DA2; however, the nutritional content was lower than that in the other treatments. Using homolactic fermentation it was possible to recycle weeds and produce ALF, which has potential as a biofertilizer according to its chemical characterization and effects shown on lettuce cultivation.